Rancang Bangun Ergonomis Alat Semprot Pestisida Jenis Gendong - Findiastuti, Weny (Universitas Trunojoyo Madura, 2009)
Mace is a pesticide applicator tool is needed in order to eradicate and control of pests and plant diseases. That is to say that this tool is one tool that should be owned btt afarmer. In the market, carrying a syringe in circulation andfarmers are often used syringe wit'h a tank model of the plate made Of iron and less attention to ersonomics. Wzth that background, it is desigJted in this study carry a syringe w!th ergon mic d szgn approaches,. methods and product development methods and approaclies bwmechamcs. Thzs study_ uses deszgn methods and product development has 4 stages, namely: the planning stage, stage of product divelopment, system-level design phase, repairs ana testing phase to implementation. The analysis was conducted by biomechanics approach. The results obtamed in this study is that there are 4 attributes custoner need to be improved ergonomics approach, namely: handle the pressure, the length of the lever, gri]J desigJt, and design backpack. After repairs done to get the product design concepts carrying Mace better, characterized by calculating the moment of the body segments long products.Keywords: Design, Ergonomics, biomechanics